Legionella colonisation in hot water systems in care homes from two Danish municipalities. (16th August 2022) - Nilsen, Niss Skov; Uldum, Søren Anker
Abstract: Legionnaires' disease is a serious health risk among the elderly. Water systems in care homes are therefore of particular interest. We investigated the levels of culturable Legionella in the hot water systems in care homes in two Danish municipalities. Two hundred and sixty-eight water samples from 98 care homes were evaluated. Contents of culturable Legionella counts were calculated, and correlations between temperature and colony-forming units (CFU/L) were analysed. Seventy-seven and 81%, respectively, of the care homes were colonised with Legionella in the two municipalities. Most care homes had less than 1, 000 CFU/L, but 13 and 16% had more than 10, 000 CFU/L. When including first flush samples, 27% of the care homes in Municipality 1 had Legionella levels above 10, 000 CFU/L. Temperatures of ≥50 °C in Municipality 1 and ≥55 °C in Municipality 2 correlated with low levels of Legionella . The content of Legionella colonies was significantly higher in care homes in Municipality 1. However, a significantly higher proportion of taps in Municipality 2 had Legionella colonies. In conclusion, temperatures should be raised to 55 °C to avoid high Legionella levels. Test procedures should be evaluated, and the regular use of taps and routine testing for Legionella should be taken into consideration. HIGHLIGHTS: Legionnaires' disease is a serious health risk among the elderly. Seventy-seven and 81% of the hot water systems in care homes from two Danish municipalities were colonised with Legionella . Water temperatures above 55 °C were related to the low contents of Legionella . Test procedures for the measurement of Legionella should be evaluated. Routines for the regular use of taps and showers should be implemented at care homes. Graphical Abstract